The Relationship of Physical Self Esteem to Achievement in the Applied Units of Physical Education Students - boualdjia omar; faresbekka (sports creativity, 2025)
The objective of this study was to determine the relationship between physical self-esteem and achievement in the applied units of the physical education students. The field study was conducted at the Institute of Science and Technology of Physical and Sports Activities at the University of Mssila, based on the self-esteem scale of Mohammed Hassan Allawi, In the achievement tests in the applied units. The results confirm that there is a positive relationship between physical self-esteem and achievement in the applied units in the students of the Department of Physical Education with a high level of both achievement and self-esteem of the students on the total score of the scale.